A survey of key protocol and application scenario of time-sensitive network - Peizhuang CONG; Ye TIAN; Xiangyang GONG; Xirong QUE; Wendong WANG (Dianxin kexue)
With the development of information technology,the demand for scenarios with objects as the main body of communication is increasing,such as factory automation control,automatic driving,etc.The time delay requirements of such communication for data transmission far exceed the controllable range of traditional ethernet,then time-sensitive network have emerged.Time-sensitive network is a standardized technology that provides deterministic information transmission based on standard ethernet.It minimizes jitter through time-aware scheduling mechanism and provides reliable guarantee of data transmission for time-sensitive applications.The core characteristics and mechanism of time-sensitive network were introduced through the description of IEEE standards and its application scenarios were analyzed in vehicle network,industrial internet,aircraft data network and mobile fronthaul network.